KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN PATIN (Pangasius djambal) YANG DIPELIHARA PADA SISTEM BUDIKDAMBER DENGAN PADAT TEBAR BERBEDA - Dini Islama; Riski Kurniawan; Mahendra Mahendra; Fitria Rahmayanti; Fazril Saputra; Mai Suriani, S.Kel., M.Si (JURNAL PERIKANAN TROPIS, 2022)
This study aimed to examine the effect of application of different stocking densities in  budikdamber system on the survival rate and growth of silver catfish (Pangasius djambal). The non-factorial Complete Randomized Design (RAL) used in this study consisted of four treatments and three tests. The treatments studied were the application of a stocking density of 5 fishes/container (P1), 10 fishes/container (P2), 15 fishes/container (P3), and  20 fishes/container (P4). The silver catfish used in this study was 6-8 cm in size. The maintenance period of silver catfish in this study was in 40 days. The research parameters that measured in this study were survival rate, absolute weight growth, absolute length growth, specific growth rate and water quality. The results of analysis of variance (ANOVA) showed that different stocking densities on rearing media with the “Budikdamber” system had no significant effect for survival rate, absolute weight growth and specific growth rate of silver catfish (Pangasius djambal), but had a significant effect on absolute length of silver catfish (Pangasius djambal). The best stocking density to increase the absolute length growth of silver catfish is 15 fishes / container (P3) in number 7.36 cm.